Separation properties of aluminium–plastic laminates in post-consumer Tetra Pak with mixed organic solvent. Issue 4 (April 2014) - Zhang, SF; Zhang, LL; Luo, K; Sun, ZX; Mei, XX
The separation properties of the aluminium–plastic laminates in postconsumer Tetra Pak structure were studied in this present work. The organic solvent blend of benzene–ethyl alcohol–water was used as the separation reagent. Then triangle coordinate figure analysis was taken to optimize the volume proportion of various components in the separating agent and separation process. And the separation temperature of aluminium–plastic laminates was determined by the separation time, efficiency, and total mass loss of products. The results show that cost-efficient separations perform best with low usage of solvents at certain temperatures, for certain times, and within a certain range of volume proportions of the three components in the solvent agent. It is also found that similar solubility parameters of solvents and polyethylene adhesives (range 26.06–34.85) are a key factor for the separation of the aluminium–plastic laminates. Such multisolvent processes based on the combined-system concept will be vital to applications in the recycling industry.